Kalman Filter-based EM-optical Sensor Fusion for Bone Needle Position Tracking - Xia, Zhiyu; Wang, Han; Men, Yulong; Ma, Haofei; Cao, Zexin; Wang, Weidong; Du, Zhijiang (IEEE sensors journal, 2024)
Pelvic fracture is a serious high-energy injury with the highest disability and mortality rate among all fractures. Therefore, the greater resetting force and more complex resetting path of the pelvic reduction robot also affect the accuracy of the navigation system.Type C pelvic fractures involve both rotational and vertical displacement, the surgical instruments are likely to be obstructed during the surgical procedure, making it difficult for traditional optical localization methods in surgical navigation to meet the requirement of unobstructed visibility. Hence, in this paper, a pelvic reduction localization and navigation method based on the fusion of electromagnetic and optical techniques is investigated to improve the positioning accuracy for achieving high resetting forces and complex resetting paths. This paper utilizes an Optical Tracking System (OTS) and an Electromagnetic Tracking System (EMTS) to determine the spatial orientation of surgical instruments. The OTS offers high optical accuracy but requires a clear line of sight, while the EMTS provides lower electromagnetic accuracy and is subject to magnetic field distortions. A high-precision dynamic measurement method for internal and external poses during fracture reduction is proposed by integrating electromagnetic tracking and optical tracking technologies, to ensure continuous tracking of surgical instruments by the navigation system even when optical line of sight is obstructed or magnetic field distortions occurs. The sensors were integrated onto the intelligent bone needle and calibrated accordingly first. Then, the error models of both electromagnetic and optical tracking systems were analyzed. Based on the error analysis, we provided global error correction for the electromagnetic tracking by using the least-squares polynomial fitting method. The fusion of optical navigation and electromagnetic navigation was achieved through Kalman filtering, enabling robust tracking of surgical instruments. Our research findings demonstrate that the fusion positioning of the OTS and the EMTS effectively compensates for short marker occlusions and provides continuous estimation of the instrument's poses, thus meeting the requirements for real-time surgical navigation applications.